FOSTERING INCLUSIVE PRACTICES IN PHYSICAL EDUCATION FOR DIVERSE PARTICIPATION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This paper explores the concept of inclusion in physical education, emphasizing the importance of creating an environment where all students, regardless of their abilities, backgrounds, or needs, can actively participate. It highlights strategies for adapting activities, promoting diversity, and ensuring equal opportunities in physical education settings. The study also examines the role of educators in fostering an inclusive atmosphere that encourages teamwork, respect, and personal growth among students.